2004
DOI: 10.1002/prop.200410169
|View full text |Cite
|
Sign up to set email alerts
|

Generalizations of the AdS/CFT correspondence

Abstract: We consider generalizations of the AdS/CFT correspondence in which probe branes are embedded in gravity backgrounds dual to either conformal or confining gauge theories. These correspond to defect conformal field theories (dCFT) or QCD-like theories with fundamental matter, respectively. Computing the quark condensate and the meson spectrum for a non-supersymmetric QCD-like theory from supergravity, we find spontaneous U(1) chiral symmetry breaking as well as the associated Goldstone boson. For another example… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
120
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 95 publications
(122 citation statements)
references
References 176 publications
(310 reference statements)
1
120
0
Order By: Relevance
“…At high temperature or density, mesons become unstable and melt into the quark-gluon plasma. This phenomenon is obtained in the gauge/gravity dual description, but is also associated with a particular first-order phase transition [18,[33][34][35][36] which is not expected to be present in QCD.…”
Section: Introductionmentioning
confidence: 69%
“…At high temperature or density, mesons become unstable and melt into the quark-gluon plasma. This phenomenon is obtained in the gauge/gravity dual description, but is also associated with a particular first-order phase transition [18,[33][34][35][36] which is not expected to be present in QCD.…”
Section: Introductionmentioning
confidence: 69%
“…The numerical values for all these meson masses tend to the no-deformation result (equation (3.19) in [16]) for large m q , that is M ∼ 2 √ 2m q /L 2 -we list them in Table III and 11.4 Table III: the mass of the pion, sigma and rho meson modes as a function of the quark mass in the low temperature dilaton flow geometry -all in units of u 0 . Above the critical temperature the physically relevant D7 embeddings in the black hole geometry [18,37,38,39,40,41] give qq = 0 for m q = 0 -there is no chiral symmetry breaking and hence no pion-like meson. The D7 can either end on the black hole horizon (small m q ) or for large enough m q it has sufficient tension to support itself away from the black hole -there is a first-order phase transition in the behaviour of (quenched) quark matter as one raises the quark mass in the plasma background.…”
Section: Aspects Of the Phase Transitionmentioning
confidence: 99%
“…At vanishing baryon density it was observed in [37] that these thermal D7-embeddings are special because in the gauge theory a phase transition appears which is dual to a geometric transition on the gravity side (see figure 3). A detailed study of this transition showed that it is of first order [40]. This study has been refined and generalized to Dp/Dq-branes in [41].…”
Section: Ads/cft At Finite Temperaturementioning
confidence: 80%
“…In this work exact analytical solutions of the heat conduction equation in an inhomogeneous medium are found. That diffusion equation which is the analog of our gravity equation of motion reads 40) with the position dependent diffusivity D(ρ). The authors of [123] show that this can be transformed into Kummer's differential equation.…”
Section: Peak Turning Behavior: Quasinormal Modes and Meson Massesmentioning
confidence: 99%
See 1 more Smart Citation